Contemporary Outcomes of Tracheostomy in Patients With Single Ventricle Heart Lesions. Issue 2 (March 2023) - Zanaboni, Dominic; Yu, Sunkyung; Lowery, Ray; Vitale, Carolyn; Sood, Vikram; Schumacher, Kurt R.
Objectives: Approximately 0.2% to 2.7% of children with congenital heart disease require a tracheostomy after cardiac surgery with the majority having single ventricle (SV) type heart lesions. Tracheostomy in SV patients is reported to be associated with high mortality. We hypothesized that short- and long-term survival of patients with SV heart disease would vary according to tracheostomy indication. Methods: This is a single center, 20-year, retrospective review of all patients with SV heart disease who underwent tracheostomy. Demographic, cardiac anatomy, surgical, intensive care unit, and hospital course data were collected. The primary outcome was survival following tracheostomy. Secondary outcome was the completion of staged palliation to Fontan. Results: In total, 25 patients with SV heart disease who underwent tracheostomy were included. Indications for tracheostomy included one or more of the following: tracheobronchomalacia (n = 8), vocal cord paralysis (n = 7), tracheal/subglottic stenosis (n = 6), primary respiratory insufficiency (n = 4), diaphragm paralysis (n = 3), suboptimal hemodynamics (n = 2), and other upper airway issues (n = 1). Survival at six months, one year, five years, and ten years was 76%, 68%, 63%, and 49%, respectively. Most patients completed Fontan palliation (64%). Patients who underwent tracheostomy for suboptimal hemodynamics and/or respiratory insufficiency had a higher mortality risk compared to those with indications of upper airway obstruction or diaphragm paralysis (hazard ratio 4.1, 95% confidence interval 1.2-13.7; P  = .02). Conclusions: Mortality risk varies according to tracheostomy indication in patients with SV heart disease. Tracheostomy may allow staged surgical palliation to proceed with acceptable risk if it was indicated for anatomic or functional airway dysfunction.